DETERMINATION OF PIT-1/HINF1 POLYMORPHISM IN HOLSTEIN AND NATIVE EAR CATTLE RAISED AS GENETIC RESOURCE IN TURKEY - M. Ozdemir (Journal of Animal and Plant Sciences, 2012)
Pit-1 gene has been identified as the pituitary specific transcription factor that regulates the expression of the growth hormone (GH) and prolactin (PRL) genes in the anterior pituitary. The use of polymorphic markers in breeding programmes could make selection more accurate and efficient. A total of 252, 181 Holstein cows and 71 native East Anatolian Red (EAR) cattle, were genotyped for polymorphism of Pit-1/Hinf1 gene by the polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) methods. In the Pit-1 gene, the frequency of AA, AB, and BB genotypes was 14, 54, and 32% for EAR, and 4, 31, and 65% for Holstein,  respectively. The frequency of A allele was 41% for EAR, and 20% for Holstein. Both populations were in Hardy-Weinberg equilibrium.
Keywords: Pit-1 gene; Polymorphism; PCR-RFLP; Genetic resource; Cattle.